1978
DOI: 10.1111/j.1365-2133.1978.tb01617.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescent tracing of cytoplasmic components involved in keratinocyte differentiation

Abstract: Sera with epidermal cytoplasmic antibodies (E.C.A.) produced by human subjects after bone marrow transplantation have been studied by indirect immunofluorescen on rabbit lip sections. These sections were used in order to give on a single specimen, areas of mucosa, of parakeratotic and of orthokeratotic epithelium. It has been demonstrated that E.C.A. distinguished the basal cell layer from the upper cell layers on the three areas. Moreover, E.C.A. were not found to react identically on mucosal, parakeratotic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Similar observations have been made in studies of epidermal cytoplasmic antibodies [24]. These reacted only with the basal cells in non-keratinized epithelium, while several additional cell layers were stained in parakeratinized and orthokeratinized epithelium.…”
Section: Discussionsupporting
confidence: 85%
“…Similar observations have been made in studies of epidermal cytoplasmic antibodies [24]. These reacted only with the basal cells in non-keratinized epithelium, while several additional cell layers were stained in parakeratinized and orthokeratinized epithelium.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, when the antibodies known to react with cytoplasmic antigens of the basal cell layer (proliferative compartment) (Saurat et al, 1978b(Saurat et al, , c, 1980 were used, they did not crossreact with thymic tissue antigens. Sun & Green (1978) and Sun (1979) have actually shown that 'keratin', as detected by an antiserum raised in rabbit against human keratin, was demonstrable in the cytoplasm of keratinocytes as well as in different tissues one of which was HC of the thymus.…”
Section: Discussionmentioning
confidence: 99%
“…Four were known to react with the antigens localized in the upper compartment of orthokeratinized epitheha giving a so called U.CYT pattern (Bystryn et al, 1978). The other three were known to react exclusively with the antigens contained within the proliferative, basal cell compartment of epidermis (the so called B.CYT pattern) regardless of the type of differentiation (ortho-, parakeratinization and mucosa) expressed by the tissue (Saurat et al, 1978b). Titres and specificities of these sera have previously been reported.…”
Section: Seramentioning
confidence: 92%
See 2 more Smart Citations